2015
DOI: 10.3109/13880209.2015.1101142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginsenoside compound K combined with cisplatin on the proliferation, apoptosis and epithelial mesenchymal transition in MCF-7 cells of human breast cancer

Abstract: Context: Breast cancer seriously harms the health of women and there are currently few therapeutic options for patients with breast cancer. Objective: Effects of ginsenoside compound K (CK) in combination with cisplatin (DDP) on the proliferation, apoptosis, and epithelial mesenchymal transition (EMT) of MCF-7 cells were studied. Materials and methods: MCF-7 cells were divided into CK (50 mmol/L) group, DDP (10 mg/L) group, CK (50 mmol/L) +DDP (10 mg/L) group, and control (CON) group. The cells in the CON grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…CK is absorbed in the gastrointestinal tract before being slowly metabolized (14,15). Several studies have indicated that CK possesses anticancer activity against a variety of tumor cell types by inhibiting cell proliferation and inducing apoptosis (16,17). CK also has antimetastatic potential in various tumor cells (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…CK is absorbed in the gastrointestinal tract before being slowly metabolized (14,15). Several studies have indicated that CK possesses anticancer activity against a variety of tumor cell types by inhibiting cell proliferation and inducing apoptosis (16,17). CK also has antimetastatic potential in various tumor cells (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Most research papers cited in this review were focused solely on the mechanisms of action and the efficiency of combined saponin/drug use, and these concerned mainly dammarane‐type saponins such as ginsenosides isolated from Panax sp. (Lee et al, ; Park et al, ; Wang et al, ; Yang et al, ; Zhang et al, ; Zhang et al, ; Zhang & Li, ). However, it is not possible to draw any conclusions concerning the potential SAR.…”
Section: Structure–activity Relationship In Combined Therapymentioning
confidence: 99%
“…Most research papers cited in this review were focused solely on the mechanisms of action and the efficiency of combined saponin/drug use, and these concerned mainly dammarane-type saponins such as ginsenosides isolated from Panax sp. (Lee et al, 2014;Park et al, 2015;Wang et al, 2015;Yang et al, 2012;Zhang et al, 2008;Zhang et al, 2009;Zhang & Li, 2016 enhanced the effect of therapy and/or reduced toxicity. It is also interesting that in most saponins one of the sugar chains is attached through an ester linkage at C-28.…”
Section: Limitations Of Saponins In Therapymentioning
confidence: 99%
“…Panax ginseng C. A. Meyer has been used for nearly 5000 years in oriental medical traditions and more recently in western medicine [19]. As the major active compound present in ginseng, CK can block glycogen synthase kinase 3b signaling [20], inhibit sphingosine kinase-1 [21], decrease the levels of reactive oxygen species [22], and increase the cisplatin sensitivity of cancer cells when co-administered with cisplatin [23].…”
Section: Introductionmentioning
confidence: 99%